2004
DOI: 10.1093/aob/mch183
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships among Hylocereus and Selenicereus Vine Cacti (Cactaceae): Evidence from Hybridization and Cytological Studies

Abstract: The ease of obtaining partially fertile F1 hybrids and the relative sequence similarity (in GISH study) suggest close genetic relationships among the taxa analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 7 publications
7
66
0
3
Order By: Relevance
“…The objective of Medel (2000) was to find defense strategies against the parasite Tristerix aphyllus; a 2-yr follow-up of Echinopsis chilensis and E. acida was conducted in northern Chile and both species were found to have high synchrony in the flowering season, which occurs from September to mid-November. All of this reinforces the idea that the observed variability could be due to the co-existence with other species with simultaneous flowering, as was found in several species of the genus Hylocereus that have a high hybridization ability between them and with the species Selenicereus (Tel-Zur et al, 2004). One of the highest CV values occurred for stem diameter; this trait could be strongly influenced by the age of the plant, which is a factor that cannot be controlled in wild populations.…”
Section: Discussion M O R P H O L O G I C a L D I V E R S I T Y O F Csupporting
confidence: 82%
“…The objective of Medel (2000) was to find defense strategies against the parasite Tristerix aphyllus; a 2-yr follow-up of Echinopsis chilensis and E. acida was conducted in northern Chile and both species were found to have high synchrony in the flowering season, which occurs from September to mid-November. All of this reinforces the idea that the observed variability could be due to the co-existence with other species with simultaneous flowering, as was found in several species of the genus Hylocereus that have a high hybridization ability between them and with the species Selenicereus (Tel-Zur et al, 2004). One of the highest CV values occurred for stem diameter; this trait could be strongly influenced by the age of the plant, which is a factor that cannot be controlled in wild populations.…”
Section: Discussion M O R P H O L O G I C a L D I V E R S I T Y O F Csupporting
confidence: 82%
“…Tel-Zur et al (2005) reported the fruit weight in the female parent (hybrids S-75 and 12-31) to be between 192 to 267 grams, depending on the pollen donor used. This trait was intermediate between the parents, indicating partial dominance or co-dominance, as was previously described for others hybrids (Tel-Zur et al, 2004.…”
Section: Phenological Characterizationsupporting
confidence: 77%
“…The initial interploid crosses between the diploid H. monacanthus as a female parent and the tetraploid H. megalanthus as a male parent resulted in the release of two triploid hybrids (named S-75 and 12-31) to growers (Tel-Zur et al, 2004). These hybrids offered better taste than their diploid female parent and larger fruits than their tetraploid male parents, but, still, their spiny peel (a dominant trait), which is characteristic of H. megalanthus, was a limitation to further cultivation.…”
Section: Phenological Characterizationmentioning
confidence: 99%
“…This notion was strengthened by performing crosses between the two species, which showed that the two can pollinate each other and produce viable seedlings (Gutman 2001). This compatibility is not necessarily an indication that the two are the same species, as we found that in vine-cacti inter-specific and even inter-generic crosses can produce viable offspring (Tel-zur et al 2004;Tel-zur et al 2011). however, it is important to note that C. jamacaru is another important genetic source for breeding.…”
Section: Taxonomymentioning
confidence: 68%